Estrategias para certificar la operación y mantenimiento del edificio administrativo de la Municipalidad de Heredia mediante el sistema de evaluación LEED O+M: EB versión 4” - Murillo-Pérez, Giannina (Instituto Tecnológico de Costa Rica, 2015)
The construction of buildings for urban development generates negative environmental impacts at all stages of the life cycle of the building, as they are responsible for a high amount of emissions of greenhouse gases and consumption of natural resources. For this reason is that sustainability has been gaining strength in the construction sector and have developed a wide variety of evaluation systems that can certified high performance sustainable buildings. Leadership in Energy and Environmental Design (LEED) is now one of the most recognized and influential global assessment system; the certification of buildings through this standard has been growing in Latin America, Costa Rica has not been the exception and is one of the pioneers of the implementation of LEED in Central America. The LEED Operation a Maintenance rating system for existing buildings (LEED O+M: EB) is a tool that allowed to implement the concept and benefits of sustainable principles in the buildings of the public sector by certifying existing buildings, providing guidelines for implementing sustainable strategies and improve environmental performance of the building. In this paper, LEED O + M evaluated the central building of the Municipality of Heredia: EB V4 and strategies to achieve the certification of the administrative building were proposed. The results show that if the institution implements the strategies proposed, it is possible to achieve a total of 60 points, which will allowed the project to achieve Gold level certification. Keywords: SUSTAINABLE CONSTRUCTION, LEED, OPERATION AND MAINTENANCE, MUNICIPALITY OF HEREDIA.
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental). Instituto Tecnológico de Costa Rica. Escuela de Química. 2015.
Keywords: Riesgos Ambientales; Edificios; Gases de invernadero; Sostenibilidad; Operaciones y Mantenimiento